2011
DOI: 10.1259/bjr/14556365
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging for monitoring prostate cancer progression in patients managed by active surveillance

Abstract: Objectives: We studied patients managed by active surveillance to determine whether there was a difference over time in apparent diffusion coefficients (ADCs) derived from diffusion-weighted MRI in those who progressed to radical treatment (progressors, n517) compared with those who did not (non-progressors, n533). Methods: 50 consecutive patients (Stage T1/2a, Gleason grade # 3+4, prostate-specific antigen (PSA) ,15 ng ml -1 , ,50% cores positive) were imaged endorectally (baseline and 1-3 years follow-up) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 20 publications
4
51
0
Order By: Relevance
“…The literature search identified 30 original articles that were included for review: 14 on magnetic resonance imaging (MRI) [8][9][10][11][12][13][14][15][16][17][18][19][20][21], 5 on serum markers [22][23][24][25][26], 5 on urinary markers [27][28][29][30][31], 4 on histopathology markers [32][33][34][35], and 2 on germline genetic markers [36,37]. Figure 1 presents the search strategy and study selection flowchart.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified 30 original articles that were included for review: 14 on magnetic resonance imaging (MRI) [8][9][10][11][12][13][14][15][16][17][18][19][20][21], 5 on serum markers [22][23][24][25][26], 5 on urinary markers [27][28][29][30][31], 4 on histopathology markers [32][33][34][35], and 2 on germline genetic markers [36,37]. Figure 1 presents the search strategy and study selection flowchart.…”
Section: Search Resultsmentioning
confidence: 99%
“…At least one suspicious region (two in most patients) was identified in 98% of patients and biopsied. These MRI-guided biopsies to suspicious areas identified PCa in just over half the lesions Morgan et al analysed AS patients who all underwent 1.5-T DW-MRI both at inclusion and follow-up (n = 50) [21]. ADC of both tumour area and whole prostate decreased during follow-up of patients who showed disease progression.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…A radiologist with 15 years of experience in endorectal prostate MRI drew free-hand regions of interest (ROIs) around the PZ and TZ on a single slice of the axial T 2 W images at the level of the verumontanum ( Figure 1). Previous data have shown that ADCs measured in normal prostate regions from parameter maps generated in this way show minimal variation with time [14]. In addition, a free-hand ROI was placed on a single slice around a dominant tumour nodule (identified as an area of hypointense signal on the T 2 W images in a biopsy-positive octant on the slice where it appeared the largest) with simultaneous visual reference to the ADC maps.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DWI provides us with distinct functional quantitative information that refl ects integrity of cellular membranes, cellular density, and extracellular space [ 15 ]. ADC is inversely correlated to Gleason score and is helpful in differentiating between low, intermediate and high-risk Gleason scores [ 16 ]. DWI also improves PCa detection when combined with T2WI, with described sensitivity and specifi city of 89 % and 91 %, respectively [ 17 ].…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%